Hubungan Antara Hasil Imunoglobulin Antigen Terhadap Kadar Trombosit Pada Pasien DBD di Klinik Pratama Rawat Inap Mutiara Hati Bandar Mataram Lampung Tengah - Riviani Asdalit; Dian Arif Wahyudi; Hardono Hardono; Giri Susanto (STIKES Columbia Asia Medan, 2025)
Dengue fever is a disease that originates from the bite of Aedes aegypti and Aedes albocpictus mosquitoes which contain the Dengue virus. Dengue virus infection is both asymptomatic and symptomatic which includes common fever, dengue fever, and dengue hemorrhagic fever including Dengue Shock syndrome (DSS). Diagnosis of dengue virus infection, with clinical symptoms, needs to be supported by blood test results in the laboratory, including platelet count and IgG IgM Dengue examination. The purpose of the study was to determine the relationship between Immunoglobulin antigen results and platelet levels in DHF patients at the Mutiara Hati Inpatient Clinic in Bandar Mataram, Central Lampung. This type of quantitative research uses a retrospective approach. The materials and data from this research were collected from the medical records at the Multiara Hati Inpatient Primary Clinic in Bandar Mataram, Central Lampung from December 2023 to September 2024. The population in this study were patients diagnosed with DHF at the Mutiara Hati Inpatient Primary Clinic with a sample of 100 samples used. With data analysis using the C Square test. The results showed that there was a relationship between the results of Iminoglobullin antigen and platelet levels in DHF patients with Chi Sqularel P-Valulel analysis: 0,001 < 0,05. It is expected that immunoglobulin antigen examination can be used as a reference to monitor the progress of Dengue Fever (DHF) patients and to detect the risk of decreased platelet levels earlier.